A Histological Study of the Renal Corpusclenephron Distribution in Iraqi Camels (Camelusdromedaries) - Ali Fayadh Bargooth1, Ahmed Saad Al-A´araji 2, Masarat Swadi Medakel2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aims: The present histological study was carried out to map the renal corpuscle nephron distribution and their histological properties in Iraqi camels(Camelusdromedaries).Materials and methods: Both kidneys from each of 10 (5 males and 5 females) adult camels were collected as soon as possible after the camels were sacrificed for human consumption purposes in a slaughterhouse. Following the preparation of tissues(cortex and medulla), the sections were slide-stained using alum hematoxylin and eosin (H&E) stain and Periodic Acid Schiff (PAS) stain. The renal corpuscle diameters (numbers and percentages) in the subcapsular area, the cortical area, andthe juxtamedullary area were measured using an ocular micrometer.Results:The findings demonstrated that the renal capsule in camels is thick.The numbers of the renal corpuscles were low in numbers in the subscapular region which keep increasing towards the midcorticaland the Juxtamedullary regions. Moreover, the camel kidney has high numbers of long-loops of Henle nephrons and low numbers of short-loop nephrons. No significant (p?0.05) differences in the renal corpuscle diameters were noticed between midcorticaland juxtamedullaryareas. However, a significant (p?0.05) decrease in diameters of the renal corpuscles was seen in the subcapsular region. In addition, two layers consist the renal corpuscleswith a tuft of capillaries. The proximal convoluted tubules (PCTs)showed wide lumens with the presence of cuboidal epithelial cells (CuECs)and spherical nuclei. The distal convoluted tubules(DCTs) displayedthe presence of CuECs (smaller and lighter than those in the PCTs with apical spherical nuclei(ASN).Large lumens and simple columnar epithelial cells (CoECs). Furthermore, PAS staining showed high positive results in the basement membrane of the renal corpuscles.Conclusion: The current histological study provides insight about the renal corpuscle nephron distribution and their histological properties in Iraqi camels(Camelusdromedaries).